Breakfast skipping and its associated factors among undergraduates in a public university in Kuala Lumpur - Moy, Foong Ming; Surin, Johari; Ismail, Y.; Mahad, R.; Tie, F.H.; Wan Ismail, W.M.A. (2009)
An analytical cross-sectional study was conducted in a public university in Kuala Lumpur among a random sample of 2665 undergraduates. The objective was to study the prevalence of breakfast skipping and its associated factors. Data collection was conducted via a self-administered pre-tested questionnaire. There were 43.5 male respondents, with Malays being the majority (58.3). The prevalence of breakfast skipping was 29.2 (95 CI: 27.3- 30.3) . The factors significantly associated with breakfast skipping (p<0.05) were age, race, accommodation, faculty and skipping dinner. As the respondents age increased, their risk of breakfast skipping was lower (OR: 0.95; 0.89 -0.99). Malays (OR: 1.94; 1.48 - 2.54), Indians (OR: 1.70; 1.08-2.66), and students from the Sabah and Sarawak indigenous communities (OR: 2.13; 1.37 - 3.33) were more likely to skip breakfast compared to their Chinese counterparts. Respondents who stayed in their own houses were also less likely to skip breakfast compared to those staying in hostel with meals catered (OR: 2.32; 1.39 -3.84), hostel with cafeteria (OR: 2.92; 1.74 -4.91) or in rented houses (OR: 2.08; 1.25-3.46). Respondents majoring in Arts & Economics had 1.40 (1.07- 1.82) times risk of breakfast skipping compared to those majoring in Life Sciences. Those who skipped dinner too had twice the odds (1.47 - 2.77) of breakfast skipping. In conclusion the prevalence of breakfast skipping among the undergraduates of this university was moderately high. Health awareness campaigns or introduction of healthy eating guidelines should be initiated for the undergraduates as well as food caterers in campus. The policy and pricing of catered food in campus should also be reviewed.